A first-principle study of electronic, thermoelectric, and optical properties of sulfur doped c-HfO2. (1st July 2022) - Kumar, Rajesh; Kumar, Ramesh; Vij, Ankush; Singh, Mukhtiyar
Abstract: In the present work, using first-principles calculations, we systematically investigated HfO2-x Sx (x = 0, 0.03, 0.06 doping concentrations) and demonstrated the enhancement in the thermoelectric and optical properties with sulfur (S)-doping. The thermodynamical stability of the studied concentrations is confirmed using convex hull formalism and also verified by phase stability diagram. The different exchange- correlation functionals are used to calculate the band gaps. It is found that using Tran-Blaha modified Becke-Johnson (TB-mBJ) functional, the estimated value of the band gap for pristine cubic-HfO2 is 5.82 eV which is in good agreement with experimentally reported value (5.80 eV). For x = 0.03 and 0.06, the band gap value reduces to 4.88 eV and 4.18 eV, respectively. The Seebeck coefficient is 248.79 μ V K −1 at 300 K for x = 0.03 and slightly increases to 294.39 μ V K −1 at 400 K for x = 0.06 due to the creation of new states in the conduction band region, which is further confirmed by the increase in effective mass with doping concentration. The calculated Seebeck coefficient for HfO2-x Sx showed p-type behaviour over the entire temperature range for all doping concentrations. A significant reduction in the electronic thermal conductivity was observed with S-doping. This further results in a high figure of merit ( ZT e ) ∼ 0.77 and 0.82 for x = 0.03 and 0.06, respectively, at 800 K. The low value of the static dielectric constant for x = 0.03 makes it compatible for electron transport. The optical properties with doping suggest an enhancement in the UV absorption range and a decrease in reflectivity in the visible and near infrared regions of the electromagnetic spectra.